2013
DOI: 10.1002/ajh.23532
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness increases acutely during sickle cell vaso‐occlusive crisis

Abstract: Background & Aims Acute vaso-occlusive crisis (VOC) in sickle cell disease (SCD) is an important cause of end-organ damage. It is estimated that 10–39% of VOC occurs with hepatic involvement. Current assessments of hepatic involvement during VOC are unsatisfactory. We investigated transient elastography (TE) as a marker of hepatic involvement, its relationship with histology, and biochemical markers during VOC. Methods SCD patients were evaluated with biochemical markers and TE at steady-state and during VOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…endothelial inflammation, haemolysis). It has already been shown by Koh et al () that TE increases during periods of increased erythrocyte sickling. ELF scores may well be confounded by the background of ongoing haemolysis and vaso‐occlusion present in patients with SCD.…”
Section: Discussionmentioning
confidence: 75%
“…endothelial inflammation, haemolysis). It has already been shown by Koh et al () that TE increases during periods of increased erythrocyte sickling. ELF scores may well be confounded by the background of ongoing haemolysis and vaso‐occlusion present in patients with SCD.…”
Section: Discussionmentioning
confidence: 75%
“…Human tissues and the ECM present different mechanical properties . This varies from very soft tissue such as the brain (1 kPa) and liver (3 kPa) to moderate stiffness including muscle and very stiff tissue, such as bone (15 MPa) . Pelham and Wang first reported that substrate stiffness could affect the motility and spread of fibroblasts and kidney epithelial cells .…”
Section: Introductionmentioning
confidence: 99%
“…3 This varies from very soft tissue such as the brain (1 kPa) and liver (3 kPa) to moderate stiffness including muscle and very stiff tissue, such as bone (15 MPa). [4][5][6][7][8] Pelham and Wang first reported that substrate stiffness could affect the motility and spread of fibroblasts and kidney epithelial cells. 9,10 Since then, there have been increasingly widespread and profound studies on substrate stiffness and cell interactions, such as adhesion, 11 migration, 12,13 cell differentiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them were about animals [36][37][38][39][40][41][42] , some of them were about MRI or MR elastography [43][44][45][46][47][48][49][50][51][52] , some of them were about other organ systems [53][54][55][56][57][58][59][60][61][62][63][64][65] , some of them were about elastography technic 28,[66][67][68][69] and some of them were about non elastography related kidney studies 70 . We excluded these articles.…”
Section: Literature Reviewmentioning
confidence: 99%